Short-term Dynamic Psychotherapy versus Sertraline in Treatment of Social Phobia - Nader-Mohammadi Moghadam, Mehryar (Iran J Psychiatry Behav Sci, 2015)
BACKGROUND: A few studies on short-term psychodynamic approach have been conducted on social phobia. OBJECTIVES: In this study, the effectiveness of short-term psychodynamic psychotherapy on the treatment of social phobia has been compared to the effectiveness of sertraline and waiting list. MATERIALS AND METHODS: In this randomized-controlled trial study, 13 male students were treated with short-term dynamic psychotherapy (McCullough method) lasting 25 sessions, 11 students received sertraline for 12 weeks, and 14 students, as the waiting list, received no intervention for 8 weeks. Participants completed the Social Phobia Inventory (SPIN) as primary efficacy variable 4 times, and were rated with Clinical Global Impression scale (CGI) and Global Assessment of Functioning (GAF) as secondary efficacy variables. The data were analyzed with analysis of variance (ANOVA), analysis of covariance (ANCOVA), general linear model repeated measures analysis of variance and Fisher exact test. RESULTS: ANCOVA showed significant differences between groups based on SPIN scores (F = 23.51, Sig. = 0.001) and Bonferroni test, as post hoc compression, showed means of both short-term dynamic therapy and sertraline therapy groups were significantly different from waiting list mean (STDP-WL: [Formula: see text] = 15.76, Sig. = 0.001), (MED-WL: [Formula: see text] = 15.91, Sig. = 0.001). Mean of SPIN scores was not significantly different between short-term dynamic psychotherapy and pharmacotherapy groups. In both treatment groups, means of SPIN scores significantly decreased in posttest, but not in waiting. These results repeated with GAF and CGI scores. CONCLUSIONS: The results indicated that short-term dynamic psychotherapy sertraline are effective in decreasing social phobia symptoms and were superior to control group.